2001
DOI: 10.1111/j.1752-1688.2001.tb05516.x
|View full text |Cite
|
Sign up to set email alerts
|

MULTIOBJECTIVE REAL‐TIME RESERVOIR OPERATION WITH A NETWORK FLOW ALGORITHM1

Abstract: A network flow algorithm has been developed for the optimization of real‐time operation of a multiple reservoir system. Two purposes have been considered in the operation: flood control and hydropower generation. A special network structure was developed which allows the consideration of river routing. A multiobjective formulation is utilized thus allowing generation of a non‐dominated curve. The effect of imperfect forecast on the performance of the real‐time operation model is also evaluated. An application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 21 publications
(14 reference statements)
0
15
0
Order By: Relevance
“…The developed models are applied to the Tanshui River Basin reservoir system in northern Taiwan. Braga and Barbosa (2001) indicated that inflow forecast reliability decreases with the increase in the forecasting time horizon. Thus, the 6 h ahead hydrological forecast data are employed to determine releases from the reservoir in the case study.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The developed models are applied to the Tanshui River Basin reservoir system in northern Taiwan. Braga and Barbosa (2001) indicated that inflow forecast reliability decreases with the increase in the forecasting time horizon. Thus, the 6 h ahead hydrological forecast data are employed to determine releases from the reservoir in the case study.…”
Section: Introductionmentioning
confidence: 96%
“…Windsor (1973) and Braga and Barbosa (2001) described an application of deterministic optimization using a linear programming (LP) model to treat the flood control problem, and using the Muskingum method for channel routing and mass balance equation for reservoir operations. Wasimi and Kitanidis (1983) discrete-time linear quadratic Gaussian (LQG) stochastic control to the real-time daily operation under flood conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Those traditional optimization methods include Linear Programming (LP) (Marino and Mohammadi, 1983;Jabr et al, 2000;Reis et al, 2006;Lu et al, 2011;Li et al, 2013), Nonlinear Programming (NLP) (Martin, 1983;Lund and Ferreira, 1996;Barros et al, 2003;Chen, 2007), Lagrangian Relaxation (LR) (Hindi and Ghani, 1991;EI-Keib et al, 1994), Quadratic Programming (QP) (Papageorgiou and Fraga, 2007), Network Flow Algorithm (NFA) (Braga and Barbosa, 2001), and Dynamic programming (DP) (Johnson et al, 1993;Raman and Chandramouli, 1996;Eum et al, 2010;Goor et al, 2011;Shokri et al, 2013), etc. They are all elitist algorithms, and have already received different degrees of success in solving CROO problems.…”
Section: Introductionmentioning
confidence: 99%
“…To develop a multireservoir operation model for a river basin system, Windsor (1973), Needham et al (2000), and Braga and Barbosa (2001) described an application of deterministic optimization using a linear programming (LP) model to treat the flood control problem, using the Muskingum method for channel routing and mass balance equation for reservoir operations. Wasimi and Kitanidis (1983) applied the discrete-time linear quadratic Gaussian (LQG) stochastic control for the real-time daily operation under flood conditions.…”
mentioning
confidence: 99%